Development of an inductive NIS thermometer - Geng, Zhuoran (2012)
Normal metal-Insulator-Superconductor (NIS) tunnel junction thermometers have been under heavy research since 1976 after Rowell and Tsui first presented thanks to their excellent sensitivity to the temperature change in millikelvin regime. In this work, we have designed and studied an inductive readout for NIS tunnel junctions by using on-chip planar inductors and a DC SQUID (Superconducting Quantum Interference Device) to develop a sensitive and fast thermometer for studies of nanoscale heat conduction and bolometry. In this thesis, the processing of the samples fabricated in Nanoscience Center in Jyväskylä are presented, and several processing challenges have been dealt with and the fabrication recipe is discussed in detail. Two measurements were performed on our sample, one with a normal DC measurement setup, and the other with a AC bias and SQUID read-out setup. Our initial results indicates that the SQUID measurement follows well the DC bias measurement and the BCS theory for the SINIS junction, and shows that it is feasible to use this scheme to directly measure the conductance of a SINIS device at audio frequencies with a good sensitivity for temperatures below 1 K for aluminum as the superconductor when voltage biased close to the superconductor energy gap.